(untitled) (Modern education and development, 2025)
In today’s digital age, the role of technology in education has become increasingly vital. This article explores the concept of innovative educational technology competence, highlighting its importance in modern teaching practices. It discusses the essential skills educators must develop to effectively integrate and innovate with digital tools. The article also addresses the benefits for students and the challenges teachers face in developing this competence, providing a comprehensive view of how education is evolving in the digital era.